Earthworms communities in native savannas and man-made pastures of the Eastern plains of Colombia - Jiménez Jaén, J.J.; Moreno, Alonso; Decaëns, Thibaud; Lavelle, Patrick M.; Fisher, Myles J.; Thomas, Richard J. (International Center for Tropical Agriculture, 2001)
This was especially due to the presence of a large glossoscolecid anecic species, Martiodrilus carimaguensis Jim\233nez and Moreno, which has been greatly favored by conversion of savanna to pasture. Endogeic species were dominant in the natural savanna whereas the anecic species accounted for the 88% of total earthworm biomass in the pasture. Total earthworm density and biomass were significantly different in the two systems studied (t-test). The results indicate a clearly positive response of earthworm communities to improved pastures, a type of land use that is increasingly adopted in moist neotropical savannas.